A Small Ligand That Selectively Binds to the G-quadruplex at the Human Vascular Endothelial Growth Factor Internal Ribosomal Entry Site and Represses the Translation - Hu, Xiao-Xia; Wang, Sheng-Quan; Gan, Shi-Quan; Liu, Lei; Zhong, Ming-Qing; Jia, Meng-Hao; Jiang, Fei; Xu, Yan; Xiao, Chao-Da; Shen, Xiang-Chun (Frontiers in Chemistry, 2021)
G-quadruplexes are believed to have important biological functions, so many small molecules have been screened or developed for targeting G-quadruplexes. However, it is still a major challenge to find molecules that recognize specific G-quadruplexes. Here, by using a combination of surface plasmon resonance, electrospray ionization mass spectrometry, circular dichroism, western- blot, luciferase assay, and reverse transcriptase stop assay, we observed a small molecule oxymatrine (OMT) that could selectively bind to the RNA G-quadruplex in 5′-untranslated regions (UTRs) of human vascular endothelial growth factor (VEGF), but could not bind to other G-quadruplexes. OMT could selectively repress the translation of VEGF in cervical cancer cells. Further, it could recognize VEGF RNA G-quadruplexes in special conformations. The results indicate that OMT may serve as a potentially special tool for studying the VEGF RNA G-quadruplex in cells and as a valuable scaffold for the design of ligands that recognize different G-quadruplexes.